Ethnic Minority Poverty in Vietnam - Baulch, Bob (World Bank, Washington, DC, 2017)
Although economic reform has brought remarkable progress in poverty reduction in Vietnam, the scale and depth of ethnic minority poverty in Vietnam presents one of the major challenges to achieving the targets for poverty reduction set out in the Socio-Economic Development Plan, as well as the millennium development goals. The authors first review a series of monetary and non-monetary indicators which show the living standards of the ethnic minorities are improving but still lag seriously behind those of the majority Kinh-Hoa. The minorities' lower living standards result from the complex interplay of overlapping disadvantages, which start in utero and continue until adult life. Next an analysis of the drivers of the ethnic gap, in terms of both differences in characteristics and differences in returns to those characteristics, is undertaken. Mean and quantile decompositions show that at least a half of the gap in per capita expenditure can be attributed to the lower returns to characteristics that the ethnic minorities receive. The reasons underlying such differences in returns are discussed, drawing on both quantitative analysis and the large number of qualitative studies on ethnic issues in Vietnam. Finally, some of the short and longer term policy measures which the authors believe could help to counter ethnic disadvantages in the nutrition, education, and employment sectors are discussed. The authors also emphasize the importance of promoting growth that is geographically broad and socially inclusive without which, the current disparities between the Kinh-Hoa and the ethnic minorities will continue to grow.